1991
DOI: 10.1203/00006450-199104000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cardiac Cycle Length on Ventricular End-Diastolic Pressure and Maximum Time Derivative of Pressure in the Stage 24 Chick Embryo

Abstract: ABSTRACT. We hypothesized that developmental in-(1) have shown that increases in both ventricular EDP and creases in both ventricular end-diastolic pressure (EDP) maximum dP/dt occur concurrently with CL decrease (heart and the maximum time derivative of pressure (dP/dt) ob-rate increase) from d 2 to 6 (Hamburger-Hamilton stages 12 to served in stage 12 to 29 chick embryos are the result of 29) of a 21-d incubation. observed cardiac cycle length (CL) decrease (heart rateWe wondered to what extent the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Early stage embryos displayed ventricular filling velocities consistent with a relatively non-compliant chamber with increasing passive filling during ventricular expansion [ 56 ]. Acute changes in heart rate produce inverse changes in ventricular pressure and SV ( Figure 5 ) [ 21 , 101 ], though dorsal aortic blood flow is maximal at intrinsic heart rates [ 102 , 103 ]. PV analysis showed that isovolumic contraction time remained independent of cycle length, while ventricular end-diastolic filling times, end diastolic volumes, and SV varied linearly with cycle length [ 104 ].…”
Section: Initial Observations On Embryonic Ventricular and Atrial mentioning
confidence: 99%
“…Early stage embryos displayed ventricular filling velocities consistent with a relatively non-compliant chamber with increasing passive filling during ventricular expansion [ 56 ]. Acute changes in heart rate produce inverse changes in ventricular pressure and SV ( Figure 5 ) [ 21 , 101 ], though dorsal aortic blood flow is maximal at intrinsic heart rates [ 102 , 103 ]. PV analysis showed that isovolumic contraction time remained independent of cycle length, while ventricular end-diastolic filling times, end diastolic volumes, and SV varied linearly with cycle length [ 104 ].…”
Section: Initial Observations On Embryonic Ventricular and Atrial mentioning
confidence: 99%